Lama kejadian loss to follow up pasien tuberkulosis paru - Munarwi, Puteri Zawaliya; Deniati, Ema Novita; Nurrochmah, Siti; Supriyadi, Supriyadi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Malang Regency ranks fourth in East Java in terms of loss to follow up (LTFU) and can have an impact on improving public health. Applicable contextual knowledge about when TB patients stop treatment and factors that predict LTFU are useful for bridging the development of time-relevant intervention approaches. There needs to be follow-up related to the management of pulmonary TB so that the number of cases can be controlled and minimized. Purpose: To determine the duration of loss to follow up in pulmonary TB patients. Method: The study used a quantitative approach that was observational analytical with a retrospective cohort study design using purposive sampling. The research sample was obtained based on data from the Tuberculosis Information System (SITB) in 2023 in the reporting records for 2023 - February 29, 2024. Data analysis was carried out univariately, bivariate using the Kaplan-Meier test, and multivariate analysis using the Cox Regression test. Results: There were differences in the age variable (p<0.001) with a predicted event at 12.1 months, employment status (p=0.041) with a predicted event at 12.1 months, and history of diabetes mellitus (DM) (p=0.004) with a predicted event at 8.0 months. However, there was no significant difference in the gender variable (p=0.099) and had a predicted event at 12.5 months. The DM history variable was the dominant variable with a risk of event of 1.9 times. Conclusion: There were differences in the variables that experienced LTFU events, including age, employment status, and history of DM. However, there was no significant difference in the gender variable. Suggestion: The importance of psychosocial support, ongoing health education, close monitoring to reduce the risk of drug withdrawal, and ensure treatment compliance. Keywords: Duration of Event; Loss to Follow Up; Tuberculosis (TB). Pendahuluan: Kabupaten Malang menempati peringkat keempat se-Jawa Timur mengenai kejadian loss to follow up (LTFU) dan dapat berpengaruh pada peningkatan derajat kesehatan masyarakat. Pengetahuan kontekstual yang berlaku tentang waktu saat pasien TB berhenti menjalani pengobatan dan faktor-faktor yang memprediksi LTFU berguna untuk menjembatani pengembangan pendekatan intervensi yang relevan dengan waktu. Perlu adanya tindak lanjut mengenai penanggulangan TB paru agar angka kasusnya dapat dikendalikan dan diminimalisir. Tujuan: Untuk mengetahui lama kejadian loss to follow up terhadap pasien tuberkulosis paru. Metode: Penelitian menggunakan pendekatan kuantitatif yang bersifat observasional analitik dengan desain studi kohort retrospektif secara purposive sampling. Sampel penelitian diperoleh berdasarkan data Sistem Informasi Tuberkulosis (SITB) tahun 2023 pada catatan pelaporan tahun 2023 – 29 Februari 2024. Analisis data dilakukan secara univariat, bivariat menggunakan uji Kaplan-Meier, dan analisis multivariat menggunakan uji Cox Regression. Hasil: Terdapat perbedaan pada variabel usia (p <0.001) dengan prediksi kejadian pada 12.1 bulan, status pekerjaan (p = 0.041) dengan prediksi kejadian pada 12.1 bulan, serta riwayat diabetes melitus (DM) (p = 0.004) dengan prediksi kejadian pada 8.0 bulan. Namun, pada variabel jenis kelamin tidak terdapat perbedaan yang signifikan (p = 0.099) dan memiliki prediksi kejadian pada 12.5 bulan. Variabel riwayat DM merupakan variabel yang dominan dengan 1.9 kali risiko kejadian. Simpulan: Terdapat perbedaan pada variabel yang mengalami kejadian LTFU, meliputi variabel usia, status pekerjaan, dan riwayat DM. Namun, pada variabel jenis kelamin tidak terdapat perbedaan yang signifikan. Saran: Pentingnya dukungan psikososial, edukasi kesehatan berkelanjutan, monitoring ketat untuk mengurangi risiko putus obat, dan memastikan kepatuhan pengobatan. Kata Kunci: Lama Kejadian; Loss to Follow Up; Tuberkulosis (TB).